FIRST DISCOVERY OF STISHOVITE IN AN IRON METEORITE - Holtstam D.; Broman C.; Söderhielm J.; Zetterqvist A. (My University, 2003)
The first occurrence of stishovite in an iron meteorite, Muonionalusta (group IVA), is reported. The mineral occurs intimately mixed with amorphous silica, forming tabular grains up to ˜3 mm wide, with a hexagonal outline. It was identified using X-ray diffraction and Raman microspectroscopy. The unit-cell parameters of stishovite are a = 4.165(3) Å and c = 2.661(6) Å, and its chemical composition is nearly pure SiO2. Raman spectra show relatively sharp bands at 231 and 754 cm−1 and a broad band with an asymmetric shape and a maximum around 500 cm−1. The rare grains are found within troilite nodules together with chromite, daubreelite, and schreibersite. From their composition and morphology, and by comparisons with silica inclusions in, e.g., the Gibeon IVA iron, we conclude that these rare grains represent pseudomorphs after tridymite. The presence of stishovite in Muonionalusta is suggested to reflect shock metamorphic conditions in the IVA parent asteroid during a cosmic impact event.